Technical and Vocational Education: It’s Importance as Perceived by Graduates of Secondary Schools in St Lucia. - Mukhari, Abd. Wahid; Augustin-Daniel, Eldrana (2005)
The purpose of this study was to investigate the importance of Technical and Vocational programmes implemented in secondary schools as perceived by the graduates of technical vocational programmes in St Lucia. A total of 267 respondents were involved in this study. From this number 114 were from technical vocational secondary schools and 153 from non technical vocational secondary schools. The study concentrated on three variables; Employment skills, career development choices and Curriculum. The survey method was used to collect data. The data collected were analyzed using Statistical Package for Social Sciences SPSS) version 11.0. Descriptive statistics and t-test was used to interpret the data collected. Both groups supported with a positive level of perception towards the three variables concentrated on. However, though both groups supported, a significant difference in their perception was indicated towards employment skills and career development choices between the two groups. The t-test showed no significant difference towards curriculum. Generally, the findings indicated that technical vocational education programmes are perceived to be important in secondary schools in St Lucia.